Green areas in Białystok - Niedzielko, Jolanta; Łochnicka, Agata (Teka Komisji Architektury, Urbanistyki i Studiów Krajobrazowych, 2019)
This work contains a description of four housing estates in Białystok from different decades of the 20th century. The approximate percentage of green areas in these states was determined based on available sources. Existing development plans were analysed with a view to the records regarding greenery. Own observations allowed to define the state of green areas – their functions, accessibility, quality and relation to space. The results of the analysis made it possible to discuss the observed problems and indicated the ways to solve them.